The Outsider Within – Commencing Fieldwork In The Kuala Lumpur/petaling Jaya Corridor, Malaysia - Nadarajah, Yaso (Penerbit Universiti Sains Malaysia (USM Press), 2007)
This article explores an ongoing research engagement with a squatter settlement community in a period of large-scale urban modernization strategies in contemporary Malaysia. This study is part of a larger local/global community sustainability research project attempting to better understand how local (and particularly poor) communities respond to and construct viable livelihoods in contemporary globalization. By positioning oneself in such places, one is also inevitably drawn into the compromised conditions of the cultural and political processes of these experiences, yet is also distanced by the fact that one does not have these everyday experiences, simply by not living in these places. This article moots the idea of an "in-betweenness of research" as one way to reflect on the post-colonial problematic of subjectivities in fieldwork. It questions the situatedness of power and knowledge, the importance of place for both researcher/subject and informant/object; and suggests that to align oneself within such an "in-betweenness" geopolitical and "neither/nor or both/and" place, while carrying out research on issues related to that very struggle is to also occupy a space of deeper scholarly understanding. While the resulting contradictions make this sort of engaged research more difficult to carry out, they also generate insight that could provide some basis for analytical understanding and theoretical innovation in a wider temporal and spatial context.